Advances in pH-responsive drug delivery systems - Yongxu Mu; Lidong Gong; Tianjiao Peng; Jun Yao; Zhiqiang Lin (Elsevier, 2021)
Bioresponsive nanosystems are increasingly important in a wide range of applications such as drug delivery, tissue engineering, imaging diagnostics and biosensors. Among these, pH-responsive delivery systems have gained considerable attention because of their ability in response to disease microenvironment and pH-triggered release of therapeutic drugs for therapy. In view of the importance of pH-sensitive nano-delivery systems, this review article highlights four types of pH-responsive modes, the corresponding design strategies, applications and future directions by smart design of pH-sensitive nanosystems for precision imaging or therapy.